γδ T-Cell Acute Lymphoblastic Leukemia/Lymphoma: Discussion of Two Pediatric Cases and Its Distinction from Other Mature γδ T-Cell Malignancies - Eric X. Wei; Vasiliki Leventaki; John K. Choi; Susana C. Raimondi; Elizabeth M. Azzato; Sheila A. Shurtleff; Menchu G. Ong; Diana M. Veillon; James D. Cotelingam; Rodney E. Shackelford (Case Reports in Hematology)
Gamma delta (γδ) T-cell antigen receptor (TCR) expression and its related T-cell differentiation are not commonly reported in T-cell acute lymphoblastic leukemia/lymphoma (T-ALL). Here we report two pediatric T-ALL cases and present their clinical features, histology, immunophenotypes, cytogenetics, and molecular diagnostic findings. The first patient is a two-year-old girl with leukocytosis, circulating lymphoblasts, and a cryptic insertion of a short-arm segment at 10p12 into the long-arm segment of 11q23 resulting in an MLL and AF10 fusion transcript, which may be the first reported in γδ T-ALL. She responded to the chemotherapy protocol poorly and had persistent diseases. Following an allogeneic bone marrow transplant, she went into remission. The second patient is an eleven-year-old boy with a normal white cell count, circulating blasts, and a normal karyotype, but without any immature cellular markers by flow cytometric analysis. He responded to the chemotherapy well and achieved a complete remission. These cases demonstrate the diverse phenotypic, cytogenetic, and molecular aspects of γδ T-ALL. Early T-precursor- (ETP-) ALL and their differential diagnosis from other mature γδ T-cell leukemia/lymphomas are also discussed.